Electronic effects in profluorescent benzotriazinyl radicals: a combined experimental and theoretical study. Issue 4 (22nd January 2021) - Exner, Jessica; Maisuls, Iván; Massolle, Anja; Klabunde, Sina; Hansen, Michael R.; Strassert, Cristian A.; Neugebauer, Johannes; Eckert, Hellmut; Studer, Armido
Abstract : The synthesis, photophysical characterization, and quantum chemical calculations of a series of benzotriazinyl radicals and their styryl radical trapping products are presented. Abstract : The synthesis, photophysical characterization, and quantum chemical calculations of a series of benzotriazinyl radicals and their styryl radical trapping products are presented. The benzotriazinyl radicals are non-luminescent but surprisingly the corresponding styryl radical trapping products exhibit high fluorescence quantum yields (up to 60% in some cases), making them highly valuable probes or labels. Additionally, the influence of the substitution pattern on the optical properties of the radical trapping products was observed experimentally and interpreted by means of quantum chemical calculations. Specific substitution patterns showed a bathochromic shift compared to the unsubstituted compound. Computationally, it was shown that this substitution pattern leads to a stronger energetic stabilization of the lowest unoccupied molecular orbital than the highest occupied molecular orbital. Analysis of the influence of the substitution pattern on the optical properties showed a bathochromic shift in several examples, which was interpreted by means of quantum chemical calculations.